The impact of digital devices on the mental and physical health of primary school children: systematic review - Megi Adrianto Yoluut; Gilang Ramadan; Giofandi Samin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The use of digital technology has permeated the lives of elementary school children, affecting aspects of their mental and physical health. While these technologies offer various benefits, there are concerns about their negative impacts such as anxiety, sleep disturbances and decreased physical activity. This study aims to evaluate the impact of digital devices on primary school children's mental and physical health through a systematic review. Using the PRISMA method, literature from PubMed, and Scopus was selected based on quality, relevance, and completeness of data. Of the initial 150 publications, 7 articles were relevant after being pre-analyzed. The results showed that physical activity is important for the health of children who actively use digital devices. Some active apps and video games increase physical activity and emotional well-being, but excessive use may pose a risk for anxiety, depression and obesity. Digital device use affects the mental and physical health of primary school children. The conclusion of this study is that parents and educators should supervise the use of digital devices to reduce negative impacts and optimally utilize technology to support children's development.